PENGUATAN KOMPETENSI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE GURU MADRASAH TSANAWIYAH MELALUI PELATIHAN PEMBELAJARAN BERBASIS ETNOPEDAGOGI - Syahraini Tambak; Desi Sukenti; M. Yusuf Ahmad; Erma Linda Siregar; Hendra Rambe (UIR Press, 2023)
The habit of madrasah tsanawiyah teachers who have not integrated educational technology in learning is an important issue in this service. Thus, the competency of technological pedagocal content knowledge by providing ethnopedagogical-based learning training is crucial to be developed by private madrasah tsanawiyah teachers in Dumai, and this is the focus of dedication. This service aims to develop technological competence pedagocal content knowledge of tsanawiyah madrasah teachers through ethnopedagogical-based learning training. Participation action research is the method used in the implementation of this service. This dedication resulted in the development of technological competence pedagocal content knowledge of madrasah tsanawiyah teachers in Dumai City through ethnopedagogical-based learning namely; prepare material in accordance with the cultural conditions of the surrounding community, namely Malay culture; create teaching materials that are integrated with the local culture being observed; designing learning plans that will be used in line with the demands of learning objectives that involve teacher skills regarding technological knowledge, pedagogical knowledge, content knowledge, pedagogical content knowledge, technological content knowledge, technological pedagogical knowledge, and technological pedagogical content knowledge or pedagogical technological knowledge and content; designing instructional media (videos) that require students to be able to integrate Malay culture with the concepts learned in madrasas that involve technological knowledge, technological content knowledge, technological pedagogical knowledge, and technological pedagogical content knowledge; Learning practice begins by exploring students' initial knowledge of culture which will be integrated into science learning and guiding students to link their culture to scientific concepts involving technological pedagogical content knowledge or knowledge of pedagogic technology and content of madrasah teachers. This dedication concludes that the development of technological competence pedagocal content knowledge of tsanawiyah madrasah teachers can develop through ethnopedagogy-based learning training.